Investigating the Impact of Business Alignment on Job Gratification in an Organization: The Case of a University in Egypt - Abdo, Said; Edgar, David (International Journal of Business, Economics and Management, 2019)
The purpose of this study was to investigate effects of business alignment and job gratifications of employees in a university, viewed as a corporate organization. This study examined if there was an empirically demonstrable connection between these two variables. This empirical research was conducted through a survey on a research sample of 200 employees of an Egyptian University. The results of this study found that there was no significant relationship between these two variables. However, it was found that employees’ job gratification can be sensitive to both positive and negative influences from certain business alignments and job gratification factors. The study concluded that there was relatively little impact of business alignment on job gratification while employee performance has only a very small impact on mediating relationship between business alignment and job gratification. Nevertheless, it is concluded that, in the university context, management should address, promote and monitor corporate intrapreneurship in the organization, eventually creating an organization with employees who are satisfied in their jobs. Managements in such organizations should therefore align themselves towards the promotion of corporate intrapreneurship activities by being receptive to, and by encouraging and rewarding innovative suggestions from employees.